Language, Ideology and Politics in Croatia - Kapović, Mate (Slavia Centralis, 2020)
Based in part on his recent book Čiji je jezik? (Who does Language Belong to?), the author reviews the intricate relation of language, ideology, and politics in Croatia in the last 20 years, including new examples and analyses. The article emphasizes problems related to Croatia specifically, which might be of interest to foreign Slavists and linguists, while the monograph (in Croatian) deals with the problems of language, society, politics, ideology, and sociolinguistics in general.